Mitigating the Adverse Effects of Night Shifts: A Review of Strategies for Enhancing Health Outcomes in Shift Workers - Wasiewicz-Ciach, Paulina; Marzec, Marcelina Teresa; Choiński, Maciej; Kuczyński, Piotr; Marszałek, Anna; Wydra-Rojek, Aleksandra; Łakoma, Aleksandra; Marzec, Weronika Zofia; Kutyla, Katarzyna; Mokot, Wojciech Jan (Quality in Sport, 2024)
Introduction and Purpose Shift work, essential for continuous operation in industries like healthcare, transportation, and security, disrupts circadian rhythms and adversely affects health. This review consolidates findings on the multifaceted impacts of night shift work, emphasizing interventions to mitigate these effects and improve worker health and well-being. Brief Description of the State of Knowledge Night shift work disrupts circadian rhythms, leading to cognitive decline, sleep disorders, mental health risks, cardiovascular issues, metabolic disturbances, and cancer susceptibility. Effective interventions include limiting shift lengths and frequency, incorporating rest breaks and napping, aligning meal times with circadian rhythms, using melatonin supplementation and light therapy to improve sleep quality, engaging in regular aerobic exercise, and employing stress management techniques. Summary Implementing proposed interventions can mitigate the adverse health effects of night shift work, enhancing worker well-being, efficiency, and job satisfaction. Tailoring strategies to different age groups optimizes effectiveness, with structured approaches beneficial for older workers and flexible options suitable for younger workers. Further research should explore long-term intervention effects and develop personalized strategies for diverse populations. This review provides comprehensive guidelines for managing the health impacts of night shift work, supporting improved patient safety, reduced accidents, and enhanced work performance across various industries.